2021
DOI: 10.47067/ramss.v4i2.137
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Energy Inflation Dynamics in Pakistan: Revisiting the Role of Structural Determinants

Abstract: Enormous fluctuation has been observed in energy prices in recent years. This strong volatility in energy prices implies grave inferences for Pakistan’s economy as shown by its substantial dependence on imported fuels. In Pakistan, energy prices play a critical role in inflation determination also concluded in the study at hand. The index of energy inflation was constructed, and the role of various control variables such as board money, taxes, oil prices, energy import, and GDP has been elaborated. Current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…So, it can be concluded that lower pump diesel and petrol prices significantly decline inflation in Pakistan. The results of this study are consistent with those of (Qasim et al, 2021;Iqbal et al, 2021;Malik, 2016;Saleem & Ahmad, 2015).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…So, it can be concluded that lower pump diesel and petrol prices significantly decline inflation in Pakistan. The results of this study are consistent with those of (Qasim et al, 2021;Iqbal et al, 2021;Malik, 2016;Saleem & Ahmad, 2015).…”
Section: Resultssupporting
confidence: 91%
“…This study is different from previous studies on the research topic as it measures energy prices in domestic pump diesel prices and pump gasoline prices. While the previous studies have measured the energy prices on the basis of international crude oil prices per barrels and ignore the cost of government taxes, transportation cost, profits of the organization (Qasim et al, 2021;Iqbal et al, 2021;Aziz et al 2016;Saleem & Ahmad, 2015). The energy prices on the basis of international crude oil prices is not a good measure of domestic energy prices.…”
Section: Figure 2 Consumer Price Index(cpi)mentioning
confidence: 99%
See 1 more Smart Citation
“…They confirm the long run association among inflation and its determinants. Iqbal et al (2021) analyzed the link between energy inflation and various control variables such as board money, taxes, oil prices, energy import, and GDP. The study explains that an increase in demand for energy in economic activities in developing countries indicates an energy demand hence infers energy inflation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…For this purpose, Augmented Dickey-Fuller test and autoregressive distributed lag model were used. It was concluded that oil price inflation does not affect economic growth in both the short and long term, but causes inflation to increase Iqbal et al (2021). applied unit root test, ADF test, Bound test, ARDL cointegration tests to the data to examine the situation in the period 1991-2019.…”
mentioning
confidence: 99%